Stunting-Free Nasyiatul Aisyiyah (Pashmina) Health Service Program for Female Students of Muhammadiyah College Kotabaru, Pontianak - Ruhama, Ufi; Yulian, Ryani; Marlenywati, Marlenywati; Khairunnisa, Intan (Pascasarjana Universitas Mataram, 2024)
This community service aims to increase the understanding of female students regarding nutrition and reproductive health. In addition, this health service activity owned by Nasyiatul Aisyiyah (PASHMINA) is a cadre program for the Regional Leadership of Nasyiatul Aisyiyah. In this activity, pengabdi conducted weight and height measurements as well as Body Mass Index (BMI) measurements. In this case there are 18 students classified as thin, 14 students classified as normal who are classified as obese less, namely 6 students. Before the material was given, the students filled out the pretest and after the presentation of the material by the resource person, the students completed the posttest. Pretest and posttest are carried out in order to determine the level of understanding of students related to the material that has been given. From the test results, it can be concluded that there is an increase in the understanding of female students by 38.98% after the material is given. This shows that the increase in understanding of female students related to stunting and reproductive health has increased. After this program is implemented, a Follow-up Plan (RTL) will be carried out between pengabdi and the Regional Leadership of Nasyiatul Aisyiyah Pontianak City in an effort to recruit early cadres in Nasyiah.